Recommendations for Child Care Centers - (:unkn) unknown (My University, 1996)
Design guide for planning, programming and designing different types of child care facilities. Includes 115 patterns for the policy, planning and design of large centers, neighborhood centers and family day-care homes. Based on current research information. Highly illustrated with photographs and sketches. Received an Award for Applied Research from Progressive Architecture, 1980, and received the 1980 UWM Foundation Research Award. Reprinted 1981, with new photographs in 1984, 1988 and in 1991. Revised edition 1994.